Mathematics
heyitsyoyo
2020-11-22 04:45:12
my daughter needs help with step by step doing this equation
ANSWERS
RoxanaLautz669
2020-11-22 05:52:13

Step 1. Multiply both sides by [latex]x+2[/latex] [latex]3x= frac{5}{9} (x+2)[/latex] Step 2. Simplify [latex] frac{5}{9} (x+2[/latex]) to [latex] frac{5(x+2)}{9}[/latex] [latex]3x= frac{5(x+2)}{9}[/latex] Step 3. Multiply both sides by 9 [latex]27x=5(x+2)[/latex] Step 4. Expand [latex]27x=5x+10[/latex] Step 5. Subtract [latex]5x[/latex] from both sides [latex]27x-5x=10[/latex] Step 6. Simplify [latex]27x-5x[/latex] to [latex]22x[/latex] [latex]22x=10[/latex] Step 7. Divide both sides by 22 [latex]x= frac{10}{22}[/latex] Step 8. Simplify [latex] frac{10}{22}[/latex] to [latex] frac{5}{11}[/latex] [latex]x= frac{5}{11}[/latex] Done! :) Decimal form if needed: 0.454545

ADD ANSWER